2009
DOI: 10.1113/jphysiol.2009.169458
|View full text |Cite
|
Sign up to set email alerts
|

Developmental alterations in the functional properties of excitatory neocortical synapses

Abstract: In the neocortex, most excitatory, glutamatergic synapses are established during the first 4-5 weeks after birth. During this period profound changes in the properties of synaptic transmission occur. Excitatory postsynaptic potentials (EPSPs) at immature synaptic connections are profoundly and progressively reduced in response to moderate to high frequency (5-100 Hz) stimulation. With maturation, this frequency-dependent depression becomes progressively weaker and may eventually transform into a weak to modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 83 publications
4
53
1
Order By: Relevance
“…At this developmental stage (P11-P15), L5 neurons also exhibit a long membrane time constant. In concert with the large amplitude and slow kinetics of uEPSPs, this will act to maximize the temporal summation of synaptic potentials and so promote activity-dependent stabilization of salient connections during cortical map refinement, consistent with findings from the somatosensory system (Feldmeyer and Radnikow, 2009). Interestingly, we observed that this transition in the properties of unitary excitatory synaptic transmission was accompanied by a marked and rapid development of the properties of presynaptic action potentials, which approached mature values by P15.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…At this developmental stage (P11-P15), L5 neurons also exhibit a long membrane time constant. In concert with the large amplitude and slow kinetics of uEPSPs, this will act to maximize the temporal summation of synaptic potentials and so promote activity-dependent stabilization of salient connections during cortical map refinement, consistent with findings from the somatosensory system (Feldmeyer and Radnikow, 2009). Interestingly, we observed that this transition in the properties of unitary excitatory synaptic transmission was accompanied by a marked and rapid development of the properties of presynaptic action potentials, which approached mature values by P15.…”
Section: Discussionmentioning
confidence: 59%
“…The use-dependent properties of synaptic transmission are particularly important for shaping information transfer at cortical connections in an activity-and frequency-dependent manner (for review, see Feldmeyer and Radnikow, 2009). We thus explored how connections in the two age groups process more complex, time-varying patterns of presynaptic AP firing.…”
Section: Development Of Synaptic Transmission Evoked By Complex Actiomentioning
confidence: 99%
“…Since quantal analysis suggested release probability to be low in the young-adult calyx of Held (Lorteije et al, 2009), it seems likely that the developmental reduction of release probability made a large contribution to the decreased impact of short-term depression. A developmental reduction of release probability has also been observed at other synapses, for example in cortex (for review, see Feldmeyer and Radnikow, 2009). …”
Section: Discussionmentioning
confidence: 81%
“…The developmental period we investigated is also characterized by significant synaptic maturation (Garaschuk et al, 2000;McCabe et al, 2007;Feldmeyer and Radnikow, 2009); determining how changing synaptic inputs interact with the developing gain-scaling properties of single cortical neurons is an open question. It is possible that intrinsic somatic properties can serve to alleviate or normalize out the effects of changes in synaptic filtering that help to shape the statistics of the input to the soma.…”
Section: Discussionmentioning
confidence: 99%